Balancing Priorities, Aligning Interests: Developing Mitigation Capacity in China and India. (March 2014) - Harrison, Tom; Kostka, Genia
Debates about how to respond to climate change have largely focused on the difficulties in agreeing on national targets for reducing greenhouse gas emissions. By assuming that the main obstacle to emissions reduction lies in the inability to reach agreement internationally, the current debate underplays the challenges of building the state capacity that will be needed to ensure mitigation takes place. The implementation of mitigation strategies is far from straightforward. It requires careful balancing of competing priorities and deliberate strategies to bring different interest groups on board. We analyze the way this balancing act has been carried out in promoting energy efficiency measures in China and India. The balancing act has been done differently as each country has tailored its approach to the specific context of competing priorities and differing state capacity. We encapsulate these differences by referring to China's approach as "state-signaling" and India's approach as a "market-plus" approach. China's approach is more explicitly statist than India's, but in both countries, the state plays a central role in building the support base for its policies through processes that we describe as the bundling of policies and interests. These bundling strategies are used to help build informal coalitions in favor of energy efficiency measures.